Lateral Entry Fixation Using Three Divergent Pins for Displaced Paediatric Supracondylar Humeral Fractures. (26th July 2011) - Guy, Stephen Paul; Ponnuru, Ramakrishna Rao; Gella, Sreenadh; Tulwa, Nirmal
Abstract : Background . Supracondylar fractures are the commonest elbow injury in children. Most displaced supracondylar fractures are manipulated and held with a medial/lateral entry or two lateral Kirschner wires. This clinical study has results purely from a three lateral divergent wire technique. Methods . Displaced supracondylar fractures were manipulated closed and three lateral divergent wires inserted. Primary study end points were range of movement and carrying angle relative to the contralateral uninjured elbow (Flynn's grading system) and presence of iatrogenic nerve or vessel injury. Results . 25 children between 3 and 10 years (median 5, range 3–10) suffered a displaced fracture (15 type III, 10 type IIB). 15 left-, 10 right-sided fractures, 14 boys and 11 girls). 23 were fixed primarily, of these 21 in the first 24 hours. 2 were delayed due to swelling. 2 were fixed secondarily with lateral k-wires after loss of position (from a primarily fixed crossed wire technique). One radial and one median nerve palsy sustained at injury settled. No iatrogenic nerve injuries occurred. 21 Excellent, 3 good and 1 poor result on Flynn's grading. Conclusions . The use of three wires on the lateral side in this cohort showed no evidence of slip in fracture position and no iatrogenic nerve injury.